Diseño de un sistema fotovoltaico para el sector residencial en la parroquia San Pedro de Vilcabamba - Flores Medina, Santiago Miguel (2023)
In the present research work, an autonomous photovoltaic system for a resident user of the San Pedro Vilcabamba parish was designed. For the system design, the methodology proposed by Ángel Bayod and the Ecuadorian Construction Standard (NEC-11, CAP.14) was used. The PVsyst 7.1 software was also used to determine in detail the losses in the system (shadow losses, the horizon losses, angular losses) with the purpose of contrasting the results with the "Worst Month" method. In addition, the PVGIS software was used to visualize the power generation of the system and the state-of-charge of the accumulation subsystem at the end of the day of the proposed configurations with the purpose of improving the state-of-charge of the battery bank. To obtain electricity consumption, the billing values of the electric company EERSSA were consulted, and the corresponding measurements and calculations were made to compare the results. The protection systems and the supports of the solar modules were designed taking into account the NEC-11 CAP.14, NEC-SB-IE and NEC-SE-CG standards. Similarly, a technical-economic analysis was carried out considering the investment amounts, equipment substitution and generated energy to apply the NPV and LCOE evaluation parameters. Finally, an environmental analysis was presented in which the CO2/MWh emission factor of the National Interconnected System was calculated to find the avoided CO2 emissions. Keywords: Photovoltaic system, electrical energy consumption, NEC-11 Chapter 14, avoided CO2 emissions